The efficiency of tropical relevant major genes in a dual purpose layer strain in the subtropical coastal region of South-East Africa - Casey, N.H. (Norman Henry) (University of Pretoria, 2013)
Thesis (PhD (Animal Science))--University of Pretoria, 2007.